36. THE STATUS OF DEPRESSION AND SOME PERSONAL, FAMILIAL AND SOCIAL FACTORS AFFECTING POST-NATAL DEPRESSION IN MOTHERS OF PRETERM BIRTH AT TWO OBSTETRIC AND GYNECOLOGICAL HOSPITALS IN HANOI (Vietnam Journal of Community Medicine, 2023)
A multi-center descriptive study was conducted among 568 mother of preterm birth from March, 2023 to June, 2023. Objectives: To describe the current status of depression and related factors to post-partum depression among mothers of preterm birth at National hospital of Obstetrics and Gynecology and Hanoi hospital of Obstetrics and Gynecology. Methodology: This is a cross-sectional study of 568 mother of preterm birth from 2 hospitals from March, 2023 to June, 2023 by using EPDS (Edinburgh Postnatal Depression Scale). The cut-off point of depression is 10. Results: The rate of depression was 27,3%. Personal and maternal lifestyle were related factors to increase the risk of depression: age ≤ 35 (OR=1,9; 95%CI=1,1-3,3), single/divorced/widow (OR=4,6; 95%CI=1,1-19,3), unwell post-partum job (OR=3,0; 95%CI=1,6-5,9), frequent use of mobile devices (OR=1,7; 95%CI=1,1-2,6). Paternal factors that increased the risk of depression including mental violence (OR=4,7; 95%CI=1,7-13,1), physical violence (OR=2,8; 95%CI=1,1-7,1), no sympathy or sharing (OR=2,1; 95%CI=1,1-4,0), frequent arguement (OR=3,2; 95%CI=1,1-9,7), male favourite ((OR=1,8; 95%CI=1,1-2,9), husband’s care during pregnancy (OR=2,2; 95%CI=1,1-4,9). Fators from family and society that inscreased the risk of depression including male favourite (OR=3,1; 95%CI=1,2-7,8), no support from family members during and after birth (OR=2,8; 95%CI=1,1-7,5), no support from family members in case of difficulty (OR=3,7; 95%CI=1,3-10,8), no support from society in case of difficulty (OR=1,5; 95%CI=1,1-2,2). Conclusion: Personal lifestyle, familial and social interventions and caring were required to decrease the rate of depression among preterm birth mothers.
Keywords: Post-partum depression, preterm birth, EPDS.